Mengoptimalkan Pemahaman Konsep dalam Sejarah Budaya Indonesia dengan Media Pembelajaran Pop-Up Book: Sebuah Studi Kuantitatif dalam Pendidikan Dasar - Soselisa, Lientje Fresty; Johannes, Nathalia Yohana; Ritiauw, Leonid; Maipauw, Musa Marsel (Jurnal Pendidikan dan Ilmu Fisika, 2025)
This study aims to examine the effect of using Pop-Up Book learning media on improving students' conceptual understanding of the material on the History of Indonesian Traditions and Culture in class III at SDN 2 Ambon. This research uses a quantitative design with a one group pre-test post-test method, involving 18 students as the sample. Data were collected through essay tests before and after the intervention, as well as through observations during the learning process. The analysis results show that the use of Pop-Up Book media significantly improved students' understanding, as reflected in the increase of the average score from 58.06 in the pre-test to 90.00 in the post-test. Additionally, the Pop-Up Book media successfully created an active and engaging learning environment, which stimulated students' curiosity and increased their participation in the learning process. The Wilcoxon Signed Rank Test statistical test showed a significant difference between the pre-test and post-test scores, with an Asymp. Sig. (2-tailed) value of 0.000, which is less than 0.05, indicating that the alternative hypothesis is accepted. Moreover, the N-Gain test produced an average value of 0.7556, which falls into the high category, indicating that the improvement in students' conceptual understanding after using the Pop-Up Book media is highly significant. This study concludes that Pop-Up Book media is effective in improving conceptual understanding of the History of Indonesian Traditions and Culture material and can be used as an innovative alternative in primary school education. Future research is recommended to expand the sample size and learning duration to test the sustainability of the effects of this media.